2015
DOI: 10.1111/cea.12626
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of specific IgE antibodies to Ses i 1 improves the diagnosis of sesame allergy

Abstract: Sensitization to Ses i 1 is strongly associated with clinical sesame allergy. Measurement of specific IgE to rSes i 1 could reduce the numbers of OFCs needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 30 publications
0
54
2
1
Order By: Relevance
“…Two of these studies reported critical values generating >95% specificity for commercial SPT, yet with sensitivities reaching <50%. In terms of specific serum IgE, >95% specificity was obtained with sensitivities <30%, while the study investigating serum reactivity to rSesi1 yielded specificity and sensitivity of 85% . SPT remains a critical diagnostic tool, in that it is a relatively straightforward inexpensive technique, with a quick readout.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of these studies reported critical values generating >95% specificity for commercial SPT, yet with sensitivities reaching <50%. In terms of specific serum IgE, >95% specificity was obtained with sensitivities <30%, while the study investigating serum reactivity to rSesi1 yielded specificity and sensitivity of 85% . SPT remains a critical diagnostic tool, in that it is a relatively straightforward inexpensive technique, with a quick readout.…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients whose BAT results for both CD63 and CD203c were below the cut-offs, 12 were not allergic and one patient was allergic. Two patients, one with SFA and one without, Regarding other methods for diagnosis of SFA, SPT, 7,9,10,17 detection of specific serum IgE against sesame protein [8][9][10]17,26 and recently, specific component testing against a recombinant Sesi 1 (rSes i1) allergen 27 have been reported in the literature. Two of these studies 7,10 reported critical values generating >95% specificity for commercial SPT, yet with sensitivities reaching <50%.…”
Section: Hpse-spt At Intermediate Critical Test Points Notably Hpsementioning
confidence: 99%
See 1 more Smart Citation
“…Almond and hazelnut are strongly birch cross‐reactive tree nuts, which can be seen in our results of the prevalence of skin prick test positivity and the asymptomatic sensitization findings in the patients that have tried these species despite of their skin prick test positivity. We consider the available species‐specific tests, when negative, sufficient to rule out hazelnut, cashew and pistachio, walnut, Brazil nut, and sesame seed allergies in most cases. Species‐specific pecan sensitizations were assessed by analysing the cross‐reactive walnut allergens .…”
Section: Discussionmentioning
confidence: 99%
“…However, to date very few studies have evaluated this technique in sesame allergy. In one study of 92 children sensitized to sesame, sensitization to a recombinant form of the protein 2S albumin (rSes i 1) had a comparable sensitivity to the commercial assay measuring sIgE (86.1% for rSes i 1 compared to 83.3% for the commercial assay) but significantly better specificity (85.7% compared to 48.2%) for sesame allergy 22. Teodorowicz et al23 identified the major allergens in six sesame-allergic patients and found that oleosin was the dominant allergen in the five patients who had a history of anaphylaxis to sesame, leading to the hypothesis that sensitization to oleosin may identify a more severe sesame-allergic phenotype.…”
Section: Diagnosismentioning
confidence: 99%